2015
DOI: 10.1093/hmg/ddv345
|View full text |Cite
|
Sign up to set email alerts
|

A role for repressive complexes and H3K9 di-methylation in PRDM5-associated brittle cornea syndrome

Abstract: Type 2 brittle cornea syndrome (BCS2) is an inherited connective tissue disease with a devastating ocular phenotype caused by mutations in the transcription factor PR domain containing 5 (PRDM5) hypothesized to exert epigenetic effects through histone and DNA methylation. Here we investigate clinical samples, including skin fibroblasts and retinal tissue from BCS2 patients, to elucidate the epigenetic role of PRDM5 and mechanisms of its dysregulation in disease. First we report abnormal retinal vascular morpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 56 publications
(82 reference statements)
0
21
0
Order By: Relevance
“…To provide a comprehensive overview of the clinical phenotype of BCS, we reviewed the data on 51 patients ( ZNF469 : n = 32; PRDM5: n = 19) (Table S1) [Al‐Hussain et al, ; Abu et al, ; Christensen et al, ; Khan et al, ; Burkitt Wright et al, ; Al‐Owain et al, ; Aldahmesh et al, ; Rohrbach et al, ; Ramappa et al, ; Avgitidou et al, ; Porter et al, ]. Only those patients with individual clinical and molecular data were included in the review.…”
Section: Brittle Cornea Syndrome (Bcs)mentioning
confidence: 99%
“…To provide a comprehensive overview of the clinical phenotype of BCS, we reviewed the data on 51 patients ( ZNF469 : n = 32; PRDM5: n = 19) (Table S1) [Al‐Hussain et al, ; Abu et al, ; Christensen et al, ; Khan et al, ; Burkitt Wright et al, ; Al‐Owain et al, ; Aldahmesh et al, ; Rohrbach et al, ; Ramappa et al, ; Avgitidou et al, ; Porter et al, ]. Only those patients with individual clinical and molecular data were included in the review.…”
Section: Brittle Cornea Syndrome (Bcs)mentioning
confidence: 99%
“…Following a comprehensive systematic review of the literature, this study found that the role of methylation in ophthalmic disease has been evaluated in histone methylation marks,41–43 gene body and promoter regions,44–53 and miRNAs,54 in the following rare ophthalmic conditions:…”
Section: Discussionmentioning
confidence: 99%
“…Brittle cornea syndrome, an autosomal recessive inherited disorder characterised by corneal fragility 42…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PRDM3 and 16 maintain mammalian heterochromatin integrity [14], while PRDM9 controls meiotic recombination [15][16][17][18][19][20]. Deregulated expression of many PRDM proteins is implicated in different types of cancers [1] and mutations in some are linked to congenital disorders [21][22][23] highlighting the importance of these proteins in normal development and disease.…”
Section: Introductionmentioning
confidence: 99%